Anesthetic Approach in a Child with Laryngocele: A Case Study - Sadeghi, Afsaneh; Memary, Elham (Annals of Anesthesiology and Critical Care, 2017)
Introduction: Herein, we report our findings of the anesthetic management of a case of laryngocele to discuss the repercussions, which need to be considered in laryngocele management, and to determine the possible pressure effects on the airway. Case Presentation: The patient was a 17-month-old girl with laryngocele, who was a candidate for surgery. Her symptoms had initiated with wheezing and occasional dysphagia. On bronchoscopy, a tracheal mass was observed, accompanied by stenosis and tracheal deviation to the right side of the neck. The patient underwent anesthesia with sevoflurane via spontaneous breathing. Anesthesia was maintained with an intravenous infusion of propofol to keep spontaneous breathing. The mass was removed by a surgeon, and after ensuring the safety of the airway, atracurium and morphine were injected intravenously. At the end of the operation, she was transferred to the pediatric intensive care unit under intubation. Conclusions: Maintenance of spontaneous ventilation during anesthesia induction is crucial in cases of laryngocele at very young age.